2020
DOI: 10.1108/bij-09-2020-0469
|View full text |Cite
|
Sign up to set email alerts
|

The effect of total quality management-enabling factors on corporate social responsibility and business performance: evidence from Vietnamese coffee firms

Abstract: PurposeThis article aims to evaluate total quality management (TQM)-enabling factors' impact on corporate social responsibility (CSR) activities and business performance through evidence from Vietnamese coffee firms.Design/methodology/approachBased on collecting data via in-depth face-to-face interviews with employees, who are working in the Vietnamese coffee companies. The partial least squares structural equation modeling (PLS-SEM) approach has been employed to investigate the relationship among the TQM-enab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 87 publications
(153 reference statements)
1
46
0
2
Order By: Relevance
“…To accomplish total quality, the organizations should apply more efforts, have more excellent knowledge and skills and behave responsibly by framing better strategies based on customer requirements (Hackman and Wageman, 1995). Do et al (2020) identified 13 total quality management enabling factors distributed under two groups, identified as human and functional. The authors established that the adoption of these factors were significant in enhancing the business performance.…”
Section: Review Of Literaturementioning
confidence: 99%
“…To accomplish total quality, the organizations should apply more efforts, have more excellent knowledge and skills and behave responsibly by framing better strategies based on customer requirements (Hackman and Wageman, 1995). Do et al (2020) identified 13 total quality management enabling factors distributed under two groups, identified as human and functional. The authors established that the adoption of these factors were significant in enhancing the business performance.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Research shows that TQM and CSR interact, which helps firms obtain superior performance as well as a sustainable competitive advantage with benefits such as an enhanced reputation, better customer satisfaction or better environmental protection. Ultimately, TQM and CSR have similarly positive effects on enhancing organizations performance, but there is a need to extend research in various sectors globally [46][47][48]. Additionally, there is no consistent conceptual framework for integrating TQM and CSR initiatives to improve organizations' performance [47,49].…”
Section: Csr and Qualitymentioning
confidence: 99%
“…Ultimately, TQM and CSR have similarly positive effects on enhancing organizations performance, but there is a need to extend research in various sectors globally [46][47][48]. Additionally, there is no consistent conceptual framework for integrating TQM and CSR initiatives to improve organizations' performance [47,49]. In relation to both concepts, TQM and CSR, there is clearly a link between CSR and quality [50].…”
Section: Csr and Qualitymentioning
confidence: 99%
“…In studies of the stakeholders' theory, the scholars agreed that businesses would enhance their profit; however, they must also assume responsibilities to the environment, community, and society where the company is operating [27]. Therefore, the CSR concept has been understood under three responsibilities dimensions: economic, social, and environmental responsibility [2,27]. Regarding supply chain management, this includes many different stages with several complex relationships between the company and other stakeholders.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The idea of conducting corporate social responsibility (CSR) has undergone phenomenal growth in recent decades and has been rolled out in diverse sectors globally, such as the European banking industry [1], Vietnamese coffee sector [2], Jordanian pharmaceutical industry [3], the U.S. restaurant industries [4], Chinese food industry [5], and so on. Indeed, this positive signal has attracted increasing interest from corporations due to the advantages of adopting CSR into their business strategy [6][7][8].…”
Section: Introductionmentioning
confidence: 99%